Antiproliferative Activity of Extracts and Fractions from Irradiated Curcuma zanthorrhiza Rhizomes Against Mouse Leukemia and Human Cancer Cell Lines - E.K. Winarno; H. Winarno; S Susanto (PPIKSN-BATAN, 2019)
Curcuma zanthorrhiza Roxb. is a medicinal plant that is used as a raw material in the herbal medicine and pharmaceutical industries. The main content of C. zanthorrhiza is curcuminoid, which is used as an antioxidant and an anticancer agent. The aim of this research was to study the effect of gamma radiation used for preserving simplicia or herbal drugs through the examination of their cytotoxicity against mouse leukemia L1210 cells and antiproliferative activity against human cancer cell lines HUT78, A549, HeLa, and THP1. The samples of curcuma rhizome were irradiated by gamma ray emitted by Cobalt-60 as a source at doses of 0 (control), 5, 7.5, 10, and 15 kGy. After irradiation, the samples were macerated using n-hexane, ethyl acetate, and ethanol, respectively. Preliminary cytotoxicity test toward extract from control sample against mouse leukemia L1210 cells revealed that the ethyl acetate extract was the most active extract inhibiting the growth of cells with an IC50 value of 16.6 µg/mL, followed by ethanol extract (18.8 µg/mL) and n-hexane extract (42.7 μg/mL). Fractionation using a chromatography column of the ethyl acetate extract resulted in seven fractions denoted as F1-F7. The cytotoxicity test of the seven fractions against mouse leukemia L1210 cells showed that fraction 3 (F3) was the most active fraction with an IC50 value of 10.0 μg/mL, followed by F7 (11.2 μg/mL), F6 (11.8 μg/mL), F5 (12.0 μg/mL), F1 (13.2 μg/mL), F4 (14.5 μg/mL), and F2 (27.8 μg/mL), respectively. Based on these results, all irradiated samples were then extracted, fractionated, and tested for cytotoxicity in a similar manner. The result showed that irradiation of samples under doses up to 10 kGy can be used to preserve Curcuma zanthorrhiza simplicia without damaging its efficacy. To ensure that the irradiation dose of 10 kGy did not reduce anticancer activity, the F3 from the irradiated sample at a dose of 10 kGy was also examined of its in-vitro antiproliferative activity using HUT78, A549, HeLa, and THP1 human cancer cell lines. The results showed that irradiation of the sample at a dose of 10 kGy reduced the antiproliferative activity of F3 against HUT78 (32 %), A549 (48 %), HeLa (42 %), and THP1 (31 %). However, its reduction did not eliminate its antiproliferative activities. These results indicated that the preservation of simplicia using radiation can be done at a maximum radiation dose of 10 kGy by modifying the concentration of simplicia in the fabrication process of herbal medicine formulation.